Linking Openness to Inclusion: A Cross-Regional Analysis of Economic Integration and Financial Access in Emerging Markets - Audi, Marc (Journal of Business and Economic Options, 2025)
This investigation evaluates the influence of economic integration on levels of financial inclusion across 32 middle-income economies between 2000 and 2023. A multidimensional index of financial inclusion is first derived by applying coefficient-of-variation weights to six core indicators that capture accessibility, utilisation, and depth of financial services. In parallel, two integration indices, i.e., global and regional, are formulated by combining conventional measures of trade openness with cross-border financial flows, thereby reflecting both goods-market and capital-market connectivity. Panel regression techniques controlling for country-specific heterogeneity and time-fixed effects reveal that deeper economic integration is associated with statistically significant improvements in financial inclusion. Moreover, the magnitude of this relationship is larger for global integration than for regional linkages, suggesting that participation in worldwide networks delivers broader financial-sector benefits than geographically limited agreements. Sub-sample analyses for Latin America, Asia, and Africa corroborate the main results, and a battery of robustness checks, including alternative weighting schemes, exclusion of crisis years, and dynamic specifications, confirms their stability. Estimation diagnostics further indicate the absence of multicollinearity and serial correlation, reinforcing confidence in the empirical strategy. Policy implications are twofold: first, middle-income governments should continue to pursue outward-oriented trade and investment policies as part of a broader agenda for inclusive finance; second, complementary domestic reforms, such as strengthening regulatory frameworks, enhancing financial literacy, and expanding digital infrastructure are indispensable for translating the gains from openness into tangible access for underserved populations. These refinements would sharpen causal inference and inform precise policy.